Predictors of Hospital Length of Stay Following Implantation of a Left Ventricular Assist Device: An Analysis of the INTERMACS Registry - Cotts, William G. (2014)
INTRODUCTION: Few studies have reported on hospital length of stay (LOS) after left ventricular assist device (LVAD) implantation. The purpose of this study was to determine pre-operative and peri-operative predictors of hospital LOS after LVAD implantation. METHODS AND MATERIALS: We analyzed adult primary continuous flow LVAD patients implanted between 6/23/06 and 12/31/10 at 105 institutions from the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS). Retrospective analyses included measures of central tendency, frequencies, correlations, and step-wise multivariable regression modeling (p≤0.05). Independent variables included demographic characteristics, pre-implant clinical and behavioral variables, and concomitant surgery. RESULTS: Characteristics of the patients (n=2,200) included a mean age of 54.6 ± 12.6 years, with 79% male, 69% white, 57% INTERMACS profile 1 or 2, 37% diabetic, 21% with history of CABG, 7% with history of valve surgery and 37% with concomitant surgery. Median hospital LOS (implant to discharge) was 20 days. Significant predictors of an increased hospital LOS included: demographic characteristics (older age and non-white), pre-implant clinical variables (history of CABG or valve surgery, diabetes, ascites, INTERMACS profiles 1 and 2, low albumin, high BUN, and high right atrial pressure), and concomitant surgery, explaining 12% variance, F=22.65, p<0.001. CONCLUSIONS: Demographic characteristics, pre-implant variables and concomitant surgery partially explained hospital LOS after continuous flow LVAD implant. These variables have implications regarding selection of patients for mechanical circulatory support.